Electroformation of quasi-two-dimensional silver patterns in the absence of supporting electrolyte - Schilardi, Patricia Laura (2003)
Quasi-two-dimensional (2D) growth patterns of silver electrodeposits obtained from aqueous silver sulfate solution in the absence of supporting electrolyte using a quasi-2D cylindrical cell involve domains with morphologies covering from dense to needle-like branching. The prevailing morphology depends on the electrolyte concentration, applied electric potential and electrolysis time. From the time dependence of the maximum radius circumscribing each electrodeposit, its dimension was obtained. The growth of the solid phase was also analysed in terms of dimensionless numbers to estimate the ionic mass-transfer contributions to the electrochemical process. For a single-growing branch the axial-to-radial growth velocity is close to 10. Phenomena promoting silver electrodeposits with irregular edges and an open structure compete with others operating in the opposite direction. These phenomena are influenced by changes in the concentration and electric potential field around the growing electrodeposit.